Impact of maternal depressive symptoms and infant temperament on early infant growth and motor development: results from a population based study in Bangladesh - Nasreen, Hashima E; Kabir, Zarina Nahar; Forsell, Yvonne; Edhborg, Maigun (Malaysian Medical Association (MMA), 2017)
Background: Evidence linking maternal depressive symptoms with infant's growth and development in low-income countries is inadequate and conflicting. This study investigated the independent effect of maternal perinatal depressive symptoms on infant's growth and motor development in rural Bangladesh. Methods: A cohort of 720 pregnant women was followed from the third trimester of pregnancy to 6-8 months postpartum. For growth and developmental outcomes, 652 infants at 2-3 months and 6-8 months were assessed. Explanatory variables comprised maternal depressive symptoms, socioeconomic status, and infant's health and temperament. Outcome measures included infant's underweight, stunting and motor development. Multiple linear regression analyses identified predictors of infant growth and development. Results: Maternal postpartum depressive symptoms independently predicted infant's underweight and impaired motor development, and antepartum depressive symptoms predicted infant's stunting. Infant's unadaptable temperament was inversely associated with infant's weight-for-age and motor development, and fussy and unpredictable temperament with height-for-age and motor development. Limitations: Repeated measures design might threaten the internal validity of the results 8.3% of the participant does not participate in the measurements at different times. As the study was conducted in two sub-districts of rural Bangladesh, it does not represent the urban scenario and cannot be generalized even for other rural areas of the country. Conclusion: This study provides evidence that maternal ante- and postpartum depressive symptoms predict infant's growth and motor development in rural Bangladesh. It is recommended to integrate psychosocial components in maternal and child health interventions in order to counsel mothers with depressive symptoms.